2015
DOI: 10.7127/rbai.v9n400307
|View full text |Cite
|
Sign up to set email alerts
|

Estacionalidade Da Evapotranspiração E Produtividade Da Água Na Microbacia Do Córrego Da Mula Em Santa Fé Do Sul – Sp

Abstract: RESUMOA microbacia do córrego da Mula se apresenta como um sócio-ecossistema sensível, com talvegues assoreados, ausência de matas ciliares e nascentes desprotegidas. A capacidade de gerar e armazenar água pela microbacia é excedida pela demanda em períodos de seca, agravando-se em secas prolongadas. Sendo assim necessário avaliar o comportamento da água acima do solo na microbacia, realizado nas épocas seca e úmida dos anos 2013 e 2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
5
2
1
Order By: Relevance
“…Evapotranspiration values of 1.2 mm day -1 were described by Anda et al (2015) and Coaguila et al (2015), corroborating the values of mean annual ET a of the IS of 1.23 mm day -1 in the studied watershed (Table 1).…”
Section: Resultssupporting
confidence: 70%
See 4 more Smart Citations
“…Evapotranspiration values of 1.2 mm day -1 were described by Anda et al (2015) and Coaguila et al (2015), corroborating the values of mean annual ET a of the IS of 1.23 mm day -1 in the studied watershed (Table 1).…”
Section: Resultssupporting
confidence: 70%
“…The highest and lowest mean of WP occurred in the autumn (4.16 kg m -3 , SDY 111) and winter (2.17 kg m -3 , SDY 255) ( Figure 2C), similar to ET a and BIO, distributed in the rainy and dry periods with annual amplitude of 1.99 kg m -3 , and again confirm the high heterogeneity of the watershed, corroborating Coaguila et al (2015), who observed mean WP values of 1.73-3.75 kg m -3 in the Mula stream's watershed.…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations